2012
DOI: 10.1111/j.1464-410x.2012.11376.x
|View full text |Cite
|
Sign up to set email alerts
|

Standard vs mini‐laparoscopic pyeloplasty: perioperative outcomes and cosmetic results

Abstract: What ' s known on the subject? and What does the study add? New techniques and instrumentation in laparoscopy including the use of ' single-port ' devices and natural orifi ce transluminal endoscopic surgery have been proposed to reduce the invasiveness of these procedures. The introduction of small laparoscopic instruments ( < 3 mm) continues to further the fi eld. To date, mini-laparoscopic instruments have been used in many urological procedures, e.g. pyeloplasty in the paediatric population. However, data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…A recent trend in LP has been the introduction of "mini laparoscopic pyeloplasty" or mLP, which utilizes 3.5 mm working trocars and a 5 mm camera port. Published results in both adults 23 and pediatric patients 24 show no significant difference in operative duration or estimated blood loss, as well as similar complication rates for LP and mLP. In the adult series, mLP was in fact associated with a shorter hospital stay and patients were more satisfied in the mLP group.…”
Section: State-of-the-art Surgical Options and Future Effortsmentioning
confidence: 96%
“…A recent trend in LP has been the introduction of "mini laparoscopic pyeloplasty" or mLP, which utilizes 3.5 mm working trocars and a 5 mm camera port. Published results in both adults 23 and pediatric patients 24 show no significant difference in operative duration or estimated blood loss, as well as similar complication rates for LP and mLP. In the adult series, mLP was in fact associated with a shorter hospital stay and patients were more satisfied in the mLP group.…”
Section: State-of-the-art Surgical Options and Future Effortsmentioning
confidence: 96%
“…Although the present series is devoid of data about patient satisfaction and scar assessment, Fiori and colleagues recently evaluated cosmetic outcomes in patients undergoing minilaparoscopic and standard pyeloplasty, by administering 3 months postoperatively a standardized questionnaire. 10 The authors found that patients who underwent the minilaparoscopic approach were significantly more satisfied with their cosmetic results than those who received standard laparoscopic pyeloplasty. Besides the comparison between ML and standard laparoscopy, it also remains to be determined the comparison between ML and LESS.…”
Section: Fig 2 Port Configuration For Different Minilaparoscopicmentioning
confidence: 97%
“…A fourth 3.5-mm trocar, placed just below the xiphoid, was used as a liver retractor in case of right-sided procedures. 10 For the retroperitoneal approach ( Fig. 2c), a retroperitoneal tunnel was created through a 6 mm skin incision below the inferior edge of the 12th rib.…”
Section: Instruments and Surgical Techniquesmentioning
confidence: 99%
See 2 more Smart Citations